Cyber Phishing dan Penegakan Hukumnya: Peran Krusial Penyidik Menurut UU ITE (RechtJiva, 2025)
Online fraud through cyber phishing techniques using electronic media has emerged as a rapidly evolving form of cybercrime, posing serious challenges to law enforcement agencies. This study aims to analyze the role of investigators in handling cyber phishing cases within the jurisdiction of the Gorontalo Regional Police and to identify the obstacles encountered during the investigation process, in accordance with Law Number 19 of 2016 concerning Electronic Information and Transactions. This research adopts an empirical juridical approach, utilizing data collected through in-depth interviews and document analysis. The findings reveal that investigators face various challenges, including limited access to digital forensic tools, the perpetrators’ use of false identities, and insufficient coordination with external institutions such as banks and internet service providers. These obstacles contribute to the low effectiveness of cyber phishing investigations, despite the increasing number of reported cases. Therefore, strengthening investigator capacity through specialized digital forensic training and establishing more systematic inter-agency coordination mechanisms are urgently needed to enhance the enforcement of laws against cyber phishing crimes.